Flexibility of platforms and its impact on platforms lifecycle: a review and a focused case - Hassan, Hamza; Ibrahim, Motasom (My University, 2021)
The market demand for differentiated product variants keeps increasing. A platform strategy is followed by companies to develop differentiated products to adapt to the forever changing customer needs while cutting the development lead times. In the automotive industry, this strategy has been used for decades to produce different variants of vehicles based around a common architecture. The longevity of platforms is expected to decrease due to the faster changing market. To fulfil the customer needs with minimal changes to the production architecture, a modular platform is a good candidate. This eliminates the hefty cost of completely redesigning a new platform or heavily modifying an existing platform architecture and its associated production setup. There is currently a lack awareness in practice of how modularisation methods can enhance the flexibility of platforms and companies generally rely on subjective approaches. This thesis was carried out in collaboration with Volvo Cars, with the goal to investigate the flexibility of the current platforms, the trade-offs required to achieve a highly flexible platform, and the role of geometry and space allocation of components regarding flexibility level. In-depth interviews were conducted with employees working at different departments at Volvo Cars. The interviews provided insights into the company’s way of working with regards to modularisation, the drawbacks with it and expected future challenges. The interview data was analysed in detail using reflective thematic analysis, comparing and categorising the data according to the relevant themes associated with the research questions. Furthermore, a case study of a component was conducted to get an understanding of the design and interfaces across vehicles of different variants. The practices followed for modularisation is at different levels of sophistication between departments at Volvo Cars, and generally trailing behind the state-of-the-art. The trade-offs identified were well understood and the qualitative analysis showed that the modularisation of pure mechanical modules is better defined and documented in comparison to electrical and software modules. The new developments like the electrification of cars pose challenges affecting the decision-making process and modularisation strategy at Volvo Cars.
Keywords: Platforms, Modularisation, Modules, Interfaces.